Aplicación móvil de gestión y control de tareas en la Clínica Cardiocentro Manta - Solorzano Zambrano, José Carlos (2020)
The present degree work focused on the development of a mobile task management and control application for the Cardiocentro Manta clinic; to reach this end, information collection was started through an interview with the manager of the company, later a study was made of similar mobile applications that are in the market, the extreme programming methodology was used for the development of the application which has four phases: in the first phase (Planning) the requirements specification document was prepared and tasks were defined, in the second phase (Design) the database and interfaces were modeled, in the third phase (Coding) each one of the defined tasks was programmed and in the last phase (Acceptance tests) unit and integration tests were carried out to check the behavior of the software and its compliance with the objectives; all this in order to be able to host the application on a cloud server to be downloaded via a link at any time, finally black box tests were carried out on the software already installed on a mobile device to check the functionality and consumption of the different services (REST API). As a result, a mobile application was obtained that is capable of handling the control and task management processes, concluding that its use in the Cardiocentro Manta clinic will have positive impacts on the performance of the personnel when executing their activities.